HLA graph, a free and ready‐to‐use bioinformatics tool to explore anti‐HLA eplets reactivity pattern. (18th June 2022) - Usureau, Cédric; Jacob, Valentine; Dubois, Valérie; Masson, Dominique; Jollet, Isabelle; Desoutter, Judith; Taupin, Jean‐Luc; Guillaume, Nicolas
Abstract : Introduction: HLA antigens are highly polymorphic, and their immunogenicity is dependent on the configurations of polymorphic amino acids. Monitoring anti‐HLA immunization is essential in organ transplantation, as antibodies directed against HLA molecules are a major cause of rejection. Anti‐HLA antibodies are not specific for HLA antigens, but recognize B‐cell epitopes present on HLA molecules. Methods: To better understand antibody reactivity patterns, we calculated the Spearman correlation of the mean fluorescence intensity (MFI) of anti‐HLA antibodies identified by a single‐antigen assay performed using a Luminex® immunobeads assay on a large number of samples. Then, we built a computer tool analyzing antibody reactivity patterns with an accessibility by a web browser linked to the International Epitope Registry. We also extended our model to Onelambda® and Lifecodes® single‐antigen class I and class II assays. Results and Discussion: The resulting MFI correlations reflect HLA antibody cross‐reactivity and eplets similarity. We built HLA Graph, a computer tool that analyzes the eplets involved in antibody reactivity profiles. HLA Graph is usable with Onelambda® and Lifecodes® single‐antigen class I and class II assays. The interpretation of reactivity against alleles not tested by the antibody assays and against the alpha and beta chains of HLA‐DQ and HLA‐DP loci were also developed. Conclusion: HLA Graph is a free and ready‐to‐use bioinformatics tool that can be used by all laboratories performing anti‐HLA antibody identification by immunobead assay.